Vasoactive-inotropic score as a predictor of clinical deterioration in pediatric patients undergoing venovenous extracorporeal membrane oxygenation: a preliminary single-center study in South Korea - Joung-Hee Byun; Young A Kim; Hye Jin Baek; Hyungtae Kim; Jae Hong Lee; Kwang Ho Choi (Acute and Critical Care, 2026)
Background: Venovenous (VV) extracorporeal membrane oxygenation (ECMO) supports pediatric patients with severe respiratory failure; however, some experience clinical deterioration requiring conversion to venoarterial (VA) ECMO or resulting in mortality. The prognostic role of the vasoactive-inotropic score (VIS) at VV ECMO cannulation remains unclear.Methods: We retrospectively analyzed pediatric patients who underwent VV ECMO between 2010 and 2024 at a single center. Baseline VIS was calculated from vasoactive infusion rates documented immediately prior to cannulation. The primary composite outcome was conversion to VA ECMO or in-hospital mortality. Associations between VIS and outcomes were assessed using correlation, univariable logistic regression, and receiver operating characteristic (ROC) analysis.Results: Twenty patients underwent VV ECMO. Five (25.0%) required VA conversion, seven (35.0%) died, and nine (45.0%) met the composite outcome. Baseline VIS was not significantly associated with isolated mode change (r=0.13, P=0.589) and showed a borderline association with mortality (r=0.43, P=0.062). Logistic regression demonstrated a consistent direction of association between higher baseline VIS and the composite outcome (odds ratio, 1.04; 95% CI, 1.00–1.09; P=0.078). Correlation analysis also suggested an association (r=0.54, P=0.014). ROC analysis demonstrated an AUC of 0.79, suggesting potential discriminative ability, with an exploratory cutoff of 25.Conclusions: Baseline VIS showed a possible association with clinical deterioration in this pilot cohort. These findings are exploratory and require validation in larger prospective multicenter studies.